2015
DOI: 10.14257/ijfgcn.2015.8.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Outlier Detection Techniques for Localization in Wireless Sensor Networks: A Survey

Abstract: In wireless sensor networks (WSNs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Outlier, which is often caused by malicious attacks, non-line-of-sight (NLoS), hardware malfunction, means abnormal measurements far beyond the normal range. There are numerous attempts that try to detect distance outliers whose distance measurement errors are significantly large and hence are most likely outliers (see [8] for a survey). For instance, Jian et al [7] use triangle inequality to detect outlier distances that are a factor of ten away from accurate measurements.…”
Section: A Noise Reduction Methodsmentioning
confidence: 99%
“…Outlier, which is often caused by malicious attacks, non-line-of-sight (NLoS), hardware malfunction, means abnormal measurements far beyond the normal range. There are numerous attempts that try to detect distance outliers whose distance measurement errors are significantly large and hence are most likely outliers (see [8] for a survey). For instance, Jian et al [7] use triangle inequality to detect outlier distances that are a factor of ten away from accurate measurements.…”
Section: A Noise Reduction Methodsmentioning
confidence: 99%
“…This table reveals how each defined technique can be applied for outlier detection in WSN based on their characteristics, usability, and drawbacks. [88,190] Spectral The detection performance is highly depending on the choices of features and distance measure Robust to parameter perturbations and good performances with different anomaly scoring metrics [117,191] Gaussian Use of the spatial correlation to determine outlying sensors and event boundaries…”
Section: Spectral Decomposition-based Approachesmentioning
confidence: 99%
“…In general, most of the existing outlier detection techniques consider outlier distances more than outlier anchors [15]. The works such as [22][23][24][25] consider distance measurement outliers, the study in [22] showed that triangle inequality had some limitations and then designed and to identify outlier distance measurements beyond triangle inequality.…”
Section: Related Workmentioning
confidence: 99%